2022
DOI: 10.1249/tjx.0000000000000193
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cognitive Impairments of Sports Concussions in College-Aged Athletes: A Meta-Analysis

Abstract: Introduction/PurposeThis meta-analysis aimed to investigate the long-term (3+ months) consequences of concussion across cognitive domains (processing speed, memory, attention, and executive functions) and subdomains in young adult athletes (university, professional, or recreational).MethodsSix databases (EMBASE, PubMed, PsycINFO, SPORTDiscus, Web of Science, and Cochrane List of Registered Trials) were searched for studies that compared cognitive performance between athletes with a history of concussion (HOC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…At the EC visit, the paper-and-pencil HVLT-R immediate recall was the sole significant predictor of group classification across batteries. While meta-analyses in adults (Belanger & Vanderploeg, 2005; Belanger et al, 2005; Redlinger et al, 2022) have shown group differences between mTBI and control groups in verbal learning, pmTBI studies to date have not supported the clinical utility of the HVLT-R. Specifically, pmTBI patients showed similar recall performance on the HVLT-R to that of controls at 7–10 days and 30-day postinjury at the group level (Newsome et al, 2016), as well as 6-month postinjury (Baillargeon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the EC visit, the paper-and-pencil HVLT-R immediate recall was the sole significant predictor of group classification across batteries. While meta-analyses in adults (Belanger & Vanderploeg, 2005; Belanger et al, 2005; Redlinger et al, 2022) have shown group differences between mTBI and control groups in verbal learning, pmTBI studies to date have not supported the clinical utility of the HVLT-R. Specifically, pmTBI patients showed similar recall performance on the HVLT-R to that of controls at 7–10 days and 30-day postinjury at the group level (Newsome et al, 2016), as well as 6-month postinjury (Baillargeon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Current literature has also been inconclusive in determining whether the cognitive effects of pmTBI are limited to the acute and SA phases of injury or extend substantially in time postinjury. While some studies have reported null findings on the lingering cognitive effects of mTBI in both pediatric and adult populations (Moore et al, 2018; Redlinger et al, 2022), other studies have indicated a subset of cognitively impaired individuals beyond what is expected in a normative sample in pediatric (5%; Babikian et al, 2013; Beauchamp et al, 2018; Iverson et al, 2006; McGrath et al, 2013; Rieger et al, 2013) and adult mTBI populations (Makdissi et al, 2010; Sicard, Caron, et al, 2021; Sicard et al, 2020). Numerous potential methodological differences can account for the discrepancies in these findings, including the heterogeneity of samples, cognitive tests employed, and assessment endpoints.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Processing speed refers to the ability to process information and complete cognitive tasks quickly and efficiently. While some studies have indicated alterations in processing speed in the days following concussion (Kontos et al, 2014) that tend to resolve by a few months post-injury (Hou et al, 2023;Robertson-Benta et al, 2023;Rohling et al, 2011), other studies have reported null findings across injury phases (Alsalaheen et al, 2021;Redlinger et al, 2022;Sicard et al, 2022;Sicard, Hergert, et al, 2021). Processing speed is closely linked to executive functioning (EF), which encompasses top-down cognitive processes responsible for planning, organizing, initiating, monitoring, and controlling goaldirected behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence in pediatric and adult samples has suggested that EF is particularly susceptible to concussion, with lower performance on EF tasks in individuals within weeks to months of a concussion relative to individuals without concussion (Baillargeon et al, 2012;Chadwick et al, 2021;Halterman et al, 2006;Howell et al, 2013;Lax et al, 2015;Loher et al, 2014;Mayr et al, 2014;Moore et al, 2014Moore et al, , 2015Moore et al, , 2016Moore et al, , 2017Moore et al, , 2019Ozen et al, 2013;Ozturk et al, 2021;Robertson-Benta et al, 2023;Sicard, Caron, et al, 2021;Sicard et al, 2018Sicard et al, , 2019Sicard et al, , 2020Sicard, Harrison, et al, 2021). A recent meta-analysis indicated that athletes with a history of concussion (at least 3 months from their last concussion) perform more poorly on EF tasks when compared to controls with no history of concussion, although no such differences were observed for other cognitive domains (Redlinger et al, 2022).…”
Section: Introductionmentioning
confidence: 99%